Från Platons grotta till PPP: Projektionernas teknikhistoria och akademikernas vardagspraktik - Kaiserfeld, Thomas (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2014)
Academics use projections in everyday practices, both in teaching and research presentations. The custom is so common it passes almost without reflection beyond what may be regarded as good and bad practices. In this article, the use of projections in research and academic teaching is exposed from Plato’s allegory of the cave via camera obscura and laterna magica to skiopticon and overhead projectors. The resulting historical narrative of the academic use of projected images revolves around their interpretation as pedagogical tool, scientific instrument and entertaining gadgetry.